2020
DOI: 10.1002/jcph.1790
|View full text |Cite
|
Sign up to set email alerts
|

Local Investigators Significantly Overestimate Overall Response Rates Compared to Blinded Independent Central Reviews in Phase 2 Oncology Trials

Abstract: The overall response rate (ORR) is a largely adopted outcome measure in early-phase oncology trials. ORR is highly relevant in cancer drug development at the time of deciding whether to move to confirmatory phase 3 trials; moreover, ORR is gaining increasing relevance in fast-track registration procedures. No systematic analysis has been conducted so far to investigate whether a discrepancy exists between ORR assessed by local investigators and those assessed by blinded reviewers in phase 2 oncology trials. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 27 publications
1
31
2
Order By: Relevance
“…Therefore, the RR reported by LIs was greater in 31 out of 36 evaluations, with an estimated mean difference of +4.57% (95% confidence interval, CI, 2.95–6.19%), thus suggesting that overall the LIs were more “optimistic” than the independent reviewers in the evaluation of tumor RR. These results are consistent with a more recent analysis carried out by our research group on data from 20 Phase 2 clinical trials having the ORR as primary or secondary endpoint, assessed by both LIs and through BICR ( Dello Russo et al, 2021 ). In some trials, more than one treatment group was included for a total of 33 ORR values.…”
Section: Local Investigator Evaluation Versus Blin...supporting
confidence: 92%
See 4 more Smart Citations
“…Therefore, the RR reported by LIs was greater in 31 out of 36 evaluations, with an estimated mean difference of +4.57% (95% confidence interval, CI, 2.95–6.19%), thus suggesting that overall the LIs were more “optimistic” than the independent reviewers in the evaluation of tumor RR. These results are consistent with a more recent analysis carried out by our research group on data from 20 Phase 2 clinical trials having the ORR as primary or secondary endpoint, assessed by both LIs and through BICR ( Dello Russo et al, 2021 ). In some trials, more than one treatment group was included for a total of 33 ORR values.…”
Section: Local Investigator Evaluation Versus Blin...supporting
confidence: 92%
“…When BICR is implemented, all the radiological images and selected clinical data acquired in the clinical trials are reviewed by independent radiologists who are blinded to treatment assignment and to any kind of clinical data that can influence the independent review process ( Ford et al, 2009 ). In this regard, we have recently observed that LIs tend to overestimate the ORR in comparison to BICR in Phase 2 clinical trials, whereas we did not find any significant evaluation bias between LIs and BICR when considering PFS in both Phase 2 and 3 trials ( Dello Russo et al, 2021 ; 2020 ). In the present article, we have tried to understand the reasons behind this discrepancy by reviewing the available evidence in the literature.…”
Section: Introductioncontrasting
confidence: 64%
See 3 more Smart Citations